“Transgenders are not dinosaurs!” Stigma faced by transgender women in their daily lives in India: implications for research and policy [version 1; peer review: 2 approved] - Ankita Mukherjee; Sandhya Kanaka Yatirajula; Pallab K Maulik; Santosh Giri (Wellcome Open Research)
Background Transgender women face stigma that adversely impacts their mental wellbeing. The stigma can be self-directed (internal), discrimination, violence and hatred directed towards them by others, mostly cis-gender persons (interpersonal stigma) and discrimination faced at the level of institutional arrangements (structural stigma). Methods This was an exploratory study that used qualitative methods of data collection (focused group discussions and in-depth interviews) to gather data from consenting adult trans women who lived in the city of Kolkata situated in the eastern state of West Bengal in India. Results The findings showed that trans women faced the trauma of non-acceptance and even rejection by their families when they began to express their chosen gender. Their gender non-conforming behaviour made them the butt of ridicule and harassment in school, resulting in many of them not finishing school. This made finding employment difficult. The trans women study participants also faced harassment at the hands of the police and from hospital staff, making them reluctant to approach the police for help and seek treatment from health providers for their physical as well as mental health concerns. Conclusions It is important for researchers to be cognizant of the challenges faced by trans women/transgender people while designing and conducting research. It is also important for policymakers to make gender affirming policies to mitigate and eliminate the stigma that transgender people are subject to thereby promoting their wellbeing.